(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Data mining is a field of computer science which commingles various traditional data analysis methods with the sophisticated algorithms to process the large amount of data. There is a rapid advancement in the data collection and the data storage technologies to cumulate such kind of vast data. To extract useful information form a greater amount of data is not an easy task.